2002
DOI: 10.1046/j.0014-2956.2001.02683.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Methylation in polylegionaminic acid is associated with the phase‐variable epitope of Legionella pneumophila serogroup 1 lipopolysaccharide

Abstract: Previously, a phase‐variable epitope was detected in the virulent wild‐type strain RC1 of Legionella pneumophila serogroup 1 subgroup OLDA using a lipopolysaccharide‐specific monoclonal antibody, mAb 2625 [Lüneberg, E., Zähringer, U., Knirel, Y. A., Steinmann, D., Hartmann, M., Steinmetz, I., Rohde, M., Kohl, J. & Frosch, M. (1998) J.␣Exp. Med.188, 49–60]. In the present study, an isogenic mutant strain, termed 5215, was constructed by deletion of genes involved in the biosynthesis of the mAb 2625 epitope. Mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…This supported the assumption that the mAb 3/1-specific epitope generated by the O -acetyltransferase Lag-1 masks the N -methyl group and hinders binding of mAb 10/6 [48]. This is in agreement with earlier observations which reported a correlation between ORF 8 and N -methylated legionaminic acid residues for the mAb 3/1 - strain RC1 [52]. However, the fact that mutants of both strains, 130b and Görlitz 6543, lost the reactivity with mAb 20/1, indicated that ORF 8 and/or ORF 11 are also involved in the generation or modification of another epitope which is not blocked by the O -acetyl group.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This supported the assumption that the mAb 3/1-specific epitope generated by the O -acetyltransferase Lag-1 masks the N -methyl group and hinders binding of mAb 10/6 [48]. This is in agreement with earlier observations which reported a correlation between ORF 8 and N -methylated legionaminic acid residues for the mAb 3/1 - strain RC1 [52]. However, the fact that mutants of both strains, 130b and Görlitz 6543, lost the reactivity with mAb 20/1, indicated that ORF 8 and/or ORF 11 are also involved in the generation or modification of another epitope which is not blocked by the O -acetyl group.…”
Section: Resultssupporting
confidence: 91%
“…It is reported that the putative methyltransferase encoded by ORF 8 is responsible for N -methylation of the 5-acetimydyol amino group of the legionaminic acid [48,52]. This is supported by studies on the legionaminic acid pathway of Campylobacter .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“… Chemical structure of L. pneumophila LPS (modified from Kooistra et al, 2002b) . Structure indicates its various regions: O-specific chain, core region consisting of the outer core and inner core and lipid A.…”
Section: The Outer Membranementioning
confidence: 99%
“…NMR experiments performed in 95% H 2 O and at lower pH (pH 3.7) revealed exchangeable NH resonances and confirmed the location of the N-methylated acetamidino group at C5 (data not shown). By comparing carbon chemical shifts to those reported for the N-methylated acetamidino structures in Legionella pneumophila (36), the 5NAm…”
Section: Hilic-ms Purification Of C Coli Vc167 Cmp-activated Metabolmentioning
confidence: 99%